1995
DOI: 10.1007/bf00202784
|View full text |Cite
|
Sign up to set email alerts
|

Human stereovision without localized image features

Abstract: Many theories of human stereovision are based on feature matching and the related correspondence problem. In this paper, we present psychophysical experiments indicating that localized image features such as Laplacian zerocrossings, intensity extrema, or centroids are not necessary for binocular depth perception. Smooth one-dimensional intensity profiles were combined into stereograms with mirror-symmetric half-images such that these localized image features were either absent or did not carry stereo informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…In recent experiments with smoothly shaded gray wedges, we have shown that stereo disparities in continuous graylevel images can be detected even though salient image features were missing and, consequently, point disparities could not be defined (Arndt et al 1995). In a systematic test of a number of potential candidates for feature matching, we showed that neither luminance edges nor luminance extrema nor the overall centroid of a gray wedge are necessary to perceive stereoscopic depth.…”
Section: Intensity-based Stereomentioning
confidence: 95%
See 4 more Smart Citations
“…In recent experiments with smoothly shaded gray wedges, we have shown that stereo disparities in continuous graylevel images can be detected even though salient image features were missing and, consequently, point disparities could not be defined (Arndt et al 1995). In a systematic test of a number of potential candidates for feature matching, we showed that neither luminance edges nor luminance extrema nor the overall centroid of a gray wedge are necessary to perceive stereoscopic depth.…”
Section: Intensity-based Stereomentioning
confidence: 95%
“…Stimuli lacking Laplacian zero-and level-crossings as well as other features have been discussed at length in Arndt et al (1995). The simplest one is a parabolic intensity profile, the second derivative of which is constant.…”
Section: Stimulusmentioning
confidence: 99%
See 3 more Smart Citations